2020
DOI: 10.1200/jco.2020.38.15_suppl.516
|View full text |Cite
|
Sign up to set email alerts
|

GAIN-2: Neo-/adjuvant phase III trial to compare intense dose-dense chemotherapy (CT) to tailored dose-dense CT in patients (pts) with high risk early breast cancer (EBC): Results on safety and interim invasive disease-free survival (iDFS).

Abstract: 516 Background: GAIN-2 (NCT01690702) compared efficacy and safety of intense, dose-dense epirubicin, nab-paclitaxel, and cyclophosphamide (iddEnPC) vs dose-dense, dose-tailored epirubicin/ cyclophosphamide followed by dose-dense, dose-tailored docetaxel (dtEC-dtD) as adjuvant or neoadjuvant CT for node-positive or high risk node-negative EBC. Here, we report safety results and interim analysis (IA) of the primary endpoint iDFS. Methods: Pts (luminal A ≥N2; luminal B N+; HER2+ and TNBC) were randomized between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Currently, HER2 + BC is defined as the overexpression of HER2 protein as detected by IHC judged as 3+ and/or FISH judged as positive (22,23). In 70-85% of the HER2 − BC, there are still low-to-moderate HER2 expression (IHC 1+/IHC 2+/FISH−) tumors known as HER2 low expression tumors (24). Previous experience of HER2 − BC indicated that it cannot be a target for conventional anti-HER2 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, HER2 + BC is defined as the overexpression of HER2 protein as detected by IHC judged as 3+ and/or FISH judged as positive (22,23). In 70-85% of the HER2 − BC, there are still low-to-moderate HER2 expression (IHC 1+/IHC 2+/FISH−) tumors known as HER2 low expression tumors (24). Previous experience of HER2 − BC indicated that it cannot be a target for conventional anti-HER2 therapy.…”
Section: Discussionmentioning
confidence: 99%